Pengelolaan Pembelajaran Agama Islam Berorientasi Nilai-Nilai Karakter Di MTS Negeri Sragen - SUWARSINI, SRI; , Prof.Dr.Bambang Sumardjoko, M.Pd; , Dr. Maryadi, M.A (2017)
The purpose of this study are 1) To describe the learning plan to Islam subjects Fiqh classes IX-oriented character values in MTs State sragen, 2) To describe the implementation of learning Islam subjects Fiqh classes IX-oriented character values at MTs Sragen, 3) describe the system of evaluation of the learning curriculum of Islam subjects Fiqh classes IX-oriented character values at MTs Sragen . This study used a qualitative approach, naturalistic ethnographic research methods. Source of data used informants, documents, places and events. Techniques of collecting data through observation, interviews, documentation. The validity of the data using triangulation techniques and triangulation of data collection sources. Technical analysis of the data used is an interactive model that consists of four main components, namely data collection, data reduction, data presentation and conclusion. The results showed that 1) Planning learning Islamic religious subjects jurisprudence Class IX oriented character values in MTs Negeri Sragen is in conformity with the components of the curriculum. Before the new school year each subject teacher has prepared a learning device. Prota, promissory notes, syllabus and lesson plans prepared as lesson preparation and in accordance with the standards of competence and basic competences to be achieved. 2) Implementation of Islamic learning subjects Fiqh Class IX oriented character values at MTs Sragen has been implemented in accordance with the components of learning. The learning objectives Fiqh subjects the students are able to understand the subject matter field of Islamic law and apply the values expected character. And material support the achievement of Competence Standard and Basic Competence and achievement indicators. The learning method used lectures, discussion and practice using learning media in the form of laptops, LCD and video learning. 3) Evaluation of the learning curriculum subjects Islamic Fiqh Class IX oriented character values at MTs Sragen used to determine the suitability of the learning plan with implementation carried out in the context of micro by teachers in learning by using CIPP evaluation model curriculum. This model emphasizes learning success of factors, learners, environments, programs and regulatory purposes that are used as well as the procedures and mechanisms for the implementation of the program itself.